MBASAAKÉ IN FAMILY CIRCLE: LINGUISTIC SOCIALIZATION OF POLITENESS IN JAVANESE - Arapa Efendi; Katharina E. Sukamto (Masyarakat Linguistik Indonesia, 2020)
This qualitative preliminary study highlights a common linguistic practice of politeness in the Javanese family circle called mbasaaké, which refers to addressing or referring to a family member with a kinship term that does not necessarily portray the actual family relationship. This study aims to demonstrate that this pragmatic practice of mbasaaké requires the role of adult speakers in the family circle to novice members of the family. The adult members in the family intentionally deployed this act as a strategy to socialize politeness in the Javanese culture. A small number of naturally occurring interactive turns which involves four family members are presented in this paper to illustrate this mbasakaké practice. The four persons who participated in the casual conversations originally come from East Java, but they have resided in Yogyakarta for many years. The data presented in this paper prove that this linguistic socialization is continuously practiced within the family circle with or without the presence of the novice members of the family. Another important finding is that a respectful kinship term is also given to a family member in absentia.